2013
DOI: 10.4236/ns.2013.55075
|View full text |Cite
|
Sign up to set email alerts
|

Somaclonal variations as a mean for obtaining regenerants with different growth rates in poplar (<i>Populus × berolinensis</i> Dipp.)

Abstract: Adventive regenerants of Populus × berolinensis Dipp. were obtained on 1/2 MS salts with sucrose, vitamins, BA, TDZ and NAA using stem, petiole and leaf explants. They differed from each other in plantlet dimensions. More than 50 clones were produced from initial regenerants by excision and rooting of apexes and lateral shoots. Differences in stem length and thickness were observed between 200 field plants produced from in vitro plantlets. Differences in stem length were conditioned mainly due to different num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…The use of cluster analysis to complement either principal coordinate or principal component analyses of morphological or genetic traits in plants is well documented (Pratta et al, 2000;Song et al, 2000;Sheidai et al, 2008Sheidai et al, , 2010Valenzuela et al, 2011;Abdellatif et al, 2012;Gamburg and Voinikov, 2013;Plazas et al, 2014). In the present study cluster analysis validated the PCOORDA plots.…”
Section: Cluster Analysissupporting
confidence: 62%
See 1 more Smart Citation
“…The use of cluster analysis to complement either principal coordinate or principal component analyses of morphological or genetic traits in plants is well documented (Pratta et al, 2000;Song et al, 2000;Sheidai et al, 2008Sheidai et al, , 2010Valenzuela et al, 2011;Abdellatif et al, 2012;Gamburg and Voinikov, 2013;Plazas et al, 2014). In the present study cluster analysis validated the PCOORDA plots.…”
Section: Cluster Analysissupporting
confidence: 62%
“…Similar approaches have been used for other tissue cultured plants such as tomato (Pratta et al, 2000), soybean (Radhakrishnan and Kumari, 2008) banana (Sheidai et al, 2008) and poplar tree (Gamburg and Voinikov, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Although, somaclonal variation in trees is usually undesirable (Tremblay et al, 1999;Breton et al 2006;Marum et al, 2009), a few useful somaclonal variants have been reported in tree species (Ahuja, 1998;Bairu et al, 2011;Krishna et al, 2016). Some of these useful variants include: height and morphological traits in poplar (Fry et al, 1997) and olive (Leva et al, 2012); disease resistance in poplar (Ostry and Ward, 2003), apple citrus, and mango (Krishna et al, 2016); different growth rates in poplar (Gamburg and Voinikov, 2013); and stress tolerance in radiata pine (Montalbán et al, 2014).…”
Section: Micropropagationmentioning
confidence: 99%